The Utilization of the OmeTV Application in Assisting the Mastery and Development of Arabic Language - Ma’arif, Kaesul; Uyuni, Yuyun Rohmatul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
The accelerating development of information technology has opened new opportunities in foreign language learning, including Arabic. One digital platform increasingly utilized by learners is OmeTV, a random video call application that enables users to interact with speakers from various countries in real time. This research aims to explore the utilization of OmeTV in developing Arabic speaking skills. The methodology employed was qualitative research with an exploratory approach, conducted through observation of five Grade XI students at SMAIT Al A’raf Tangerang who had used the application for over one month. The findings indicate that OmeTV contributes significantly to the improvement of speaking fluency, vocabulary expansion (mufradāt), understanding of Arabic dialects, and an increase in students’ communication self-confidence. However, the platform also presents several drawbacks, such as the potential for exposure to inappropriate content and challenging dialect variations. This study concludes that utilizing OmeTV can serve as an effective alternative learning medium, provided it is implemented with appropriate supervision and pedagogical guidance. Suggested learning implications include establishing conversation topics, compiling keyword lists, and applying the Project-Based Learning model to maximize learning outcomes.